Marketing Strategy For Getuk Eco Products To Msmes In Magelang City - Lina Nur Liasari; Enik Rahayu (International Conference On Digital Advanced Tourism Management And Technology, 2023)
Marketing strategy is important to measure the success of a business. This study aims to determine the strategies and constraints in marketing Getuk Eco. The type of research used is qualitative research with descriptive research. The results of this study indicate that Getuk Eco has implemented a marketing mix strategy that uses the 4P variables, namely Product, Price, Place and Promotion which can increase profits and sales of Getuk Eco products. In this study, there are supporting factors and inhibiting factors for the implementation of marketing strategies for Getuk Eco product sales, which are supporting factors, namely support from the co mmunity, good service and good management. Meanwhile, the factors that hinder the implementation of the marketing strategy for Getuk Eco products are that a good organizational structure has not been formed, the workforce or human resources are still low, and the stock of banknotes is limited.